A SFB Jubilee Odyssey - Molgaard-Hansen, R. (Journal of Information and Knowledge, 1976)
A short historic account of the activities of the joint FID/CIB International Building Classification Committee (IBCC) concerning the use of the UDC and SfB systems as authorized tools for developing worldwide uniformity in the classification and indexing of building information. Significant features of the development work are shown to be consistent with the trends in documentary classification in general in recent years.